A Peircean Semiotic Analysis of Herborist Handbody Advertisements (Sastra Inggris UNPAM, 2025)
Advertising plays a crucial role in modern marketing by attracting consumers and encouraging purchases. Every advertisement uses specific signs to engage customers. This research aims to identify the signs present in Herborist handbody advertisements and examine their role in visual communication. Using a qualitative descriptive method and image analysis, the researcher analyzed 23 data points, including 11 icons, 8 indexes, and 4 symbols. The findings reveal that icons and indexes are the most dominant elements, significantly influencing the advertisement's message. Icons serve as visually appealing representations that capture the audience's attention and create positive associations with the product, reinforcing beauty and self-care ideals. Meanwhile, indexes establish connections between product usage and expected results, fostering trust and confidence among consumers. By integrating these two components, the advertisement constructs a compelling narrative that draws attention and encourages consumer engagement. The prominence of icons and indexes highlights the critical role of semiotic elements in effective advertising, demonstrating their ability to enhance communication and spark consumer interest